Pengelolaan Pendidikan Karakter Disiplin Dalam Pembelajaran PKN Di SDN 4 Suru Kabupaten Grobogan - Darsono, Darsono; , Prof. Bambang Sumardjoko, M,Pd; , Dr. Sabar Narimo, M.M., M.Pd (2016)
The purpose of this research is describe the character education planning, implementation, and evaluation of student discipline character education in civics lesson at SDN 4 Suru Subdistrict Geyer, Grobogan. Metoda and Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulation. The results of this study include were Teaching Civics National Character Discipline based on the student at SD Negeri 4 Suru Geyer Subdistrict Grobogan using the curriculum SBC. In civics lesson plans and implementations are 7 characters discipline imparted to students include time discipline, discipline clothes, learning discipline, discipline of maintaining cleanliness, discipline to follow the activities of the school, the discipline of worship and social discipline. Implementation of character education student discipline in learning civics, real has increased discipline students for adhering to school that rules apply them are students who come to school late is reduced, students dressed in accordance with applicable regulations, students doing homework is no longer in school, students are more independent in learning with the declining culture of cheating, the student when leaving school / do not attend school leave certificate / permission to the school. Student achievement especially on civics lesson well from class I to class VI increased, 80% more students have reached KKM (Criterion Complete Minimal) for KKM set of 7.